Social work and telehealth: How Patient Aligned Care Team (PACT) social workers in the Veterans Health Administration responded to COVID-19. (7th February 2021) - Cornell, Portia Y.; Celardo, Caitlin; Chmelka, GinaR.; Giles, Angela J.; Halladay, Christopher W.; Halaszynski, Jaime; Montano, Anna-Rae; Rudolph, James L.; Silva, Jennifer W.
ABSTRACT: In March 2020, the Veterans Health Administration (VA) responded to pandemic shutdowns with a rapid pivot toward providing services via telehealth. Using data on Veterans who received interventions from social workers between 2019 and 2020 at sites that participated in a national program to increase social work staffing in primary care, we examined changes in frequency and modality of social work encounters that occurred with the onset of the COVID-19 pandemic. We found that primary care social workers maintained a consistent level of engagement, with increases in telephone and video telehealth encounters as in-person visits decreased. Through front-line perspectives, we discuss the practical innovations and policies that enabled those changes in care from VA primary care social workers.